2007
DOI: 10.1080/14613800601127569
|View full text |Cite
|
Sign up to set email alerts
|

The predictive relationship between achievement and participation in music and achievement in core Grade 12 academic subjects

Abstract: The relationship between musical training and general intellectual capacity as well as academic achievement has been discussed in numerous contexts. In our study, we examined the relationship between participation and achievement in music and achievement in academic courses, based on data from three consecutive British Columbia student cohorts. Across the three cohorts, we consistently found that music participation was associated with generally higher academic achievement, and that Grade 11 music course score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 22 publications
4
28
0
3
Order By: Relevance
“…Even though this test is widely used for measuring musical aptitude, there are some limitations regarding the validity of the test. For instance, studies reported inconsistent results for the two subtests which show deviations from the published norms [ 72 , 73 ]. Another investigation noted that especially the internal reliability of the rhythm subtest should be treated with caution for grade 1 students and kindergarten children [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even though this test is widely used for measuring musical aptitude, there are some limitations regarding the validity of the test. For instance, studies reported inconsistent results for the two subtests which show deviations from the published norms [ 72 , 73 ]. Another investigation noted that especially the internal reliability of the rhythm subtest should be treated with caution for grade 1 students and kindergarten children [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown an association between music training and improvement in cognitive skills. Cross-sectional studies have shown that musicians are superior to non-musicians on verbal (Chan et al, 1998 ; Forgeard et al, 2008 ; Chobert et al, 2011 ), spatial (Helmbold et al, 2005 ; Stoesz et al, 2007 ), mathematical (Cheek and Smith, 1999 ; Gouzouasis et al, 2007 ), and general cognitive abilities (Schellenberg, 2011 ). For example, Schellenberg ( 2011 ) revealed that musically trained children had a higher general intelligence (Wechsler Abbreviated Scale of Intelligence; Wechsler, 1999 ) than did untrained children, and this difference remained when demographic variables (parents' education, parents' first language, family income, and non-musical out-of-school activities) were held constant.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these students were found to be more likely to read books and play musical instruments. As current literature shows the potential for increased academic skills with playing music [27], and with reading [28], the overall activity patterns of these students are likely to support enhanced academic skills.…”
Section: Discussionmentioning
confidence: 99%